Entropía en VQ-VMF de señal E.C.G - Aparicio Pico, Lilia Edith; Bernal R, Giovanni Alejandro; Sánchez C., Juan Manuel (Ingeniería, 1999)
This article describes the information measuring process carried by the generated output data from a Wave Shape Mean Value Vectorial Quantifier. Three data delivered by the process are taken into account, i.e., the mean value, the clasifier and the code book index. This is for every 40 samples of the E.C.G. signal. The mean value was grouped in 9 different states, the clasifier and index code book were gruoped together in 29 states. The samples were taken out from 400 E.C.G. signals.